Blue light-emitting diode phototherapy presents in vitro efficacy against distinct Leishmania species and is therapeutic against tegumentary leishmaniasis in BALB/c mice - Pimenta, Breno Luiz; Lage, Daniela Pagliara; Freitas, Camila Simões de; Vale, Danniele Luciana; Falcão, Karolina Oliveira de Melo; Dias, Saulo Samuel Gonçalves; Câmara, Raquel Soares Bandeira; Pereira, Isabela Amorim Gonçalves; Silva, Ana Luiza; Duarte Júnior, Lauro de Assis; Chavez-Fumagalli, Miguel Angel; Bianchi, Rodrigo Fernando; et al. (Frontiers in Immunology, 2025)
The treatment of tegumentary leishmaniasis (TL) faces significant challenges, including drug toxicity, high costs, and the emergence of resistant strains. These limitations highlight the urgent need for novel antileishmanial agents and therapeutic strategies. This study evaluated blue light-emitting diode (LED) phototherapy as an alternative approach to inhibit Leishmania stationary promastigotes and treat infected mammalian models. In vitro assays using Leishmania amazonensis, L. braziliensis, and L. infantum demonstrated that blue LED significantly inhibited parasite growth during and after treatment, with inhibition levels comparable to those achieved with amphotericin B (AmpB). Treatment of infected macrophages with blue LED substantially reduced infection rates and amastigote recovery across all three parasite species. Ultrastructural analyses revealed the destruction of internal organelles and alterations to the surface membranes of all Leishmania species following blue LED exposure. In in vivo experiments, L. amazonensis-infected BALB/c mice were treated with AmpB, blue LED alone, combination of blue LED plus AmpB, or saline as a control. Animals treated with blue LED, particularly in combination with AmpB, exhibited significant reductions in parasite loads in infected tissues such as lesions, spleens, livers, and draining lymph nodes, as confirmed by limiting dilution assays and qPCR. Additionally, these treatments induced a robust antileishmanial Th1-type immune response, characterized by increased production of IFN-γ, IL-12, nitrite, and IgG2a antibodies. These findings suggest that blue LED phototherapy holds promise as a potential therapeutic strategy for TL and warrants further investigation in future studies.